Identification and characterization of miRNAs in ripening fruit of Lycium barbarum L. using high-throughput sequencing - Zeng, Shaohua; Liu, Yongliang; Pan, Lizhu; Hayward, Alice; Wang, Ying (Frontiers in Plant Science, 2015)
MicroRNAs (miRNAs) are master regulators of gene activity documented to play central roles in fruit ripening in model plant species, yet little is known of their roles in Lycium barbarum L. fruits. In this study, miRNA levels in L. barbarum fruit samples at four developmental stages, were assayed using Illumina HiSeqTM2000. This revealed the presence of 50 novel miRNAs and 38 known miRNAs in L. barbarum fruits. Of the novel miRNAs, 36 were specific to L. barbarum fruits compared with L. chinense. A number of stage-specific miRNAs were identified and GO terms were assigned to 194 unigenes targeted by miRNAs. The majority of GO terms of unigenes targeted by differentially expressed miRNAs are ‘intracellular organelle’, ‘binding’, ‘metabolic process’, ‘pigmentation’, and ‘biological regulation’. Enriched KEGG analysis indicated that nucleotide excision repair and ubiquitin mediated proteolysis were over-represented during the initial stage of ripening, with ABC transporters and sulfur metabolism pathways active during the middle stages and ABC transporters and spliceosome enriched in the final stages of ripening. Several miRNAs and their targets serving as potential regulators in L. barbarum fruit ripening were identified using quantitative reverse transcription polymerase chain reaction. The miRNA-target interactions were predicted for L. barbarum ripening regulators including miR156/157 with LbCNR and LbWRKY8, and miR171 with LbGRAS. Additionally, regulatory interactions potentially controlling fruit quality and nutritional value via sugar and secondary metabolite accumulation were identified. These include miR156 targeting of fructokinase and 1-deoxy-D-xylulose-5-phosphate synthase and miR164 targeting of beta-fructofuranosidase. In sum, valuable information revealed by small RNA sequencing in this study will provide a solid foundation for uncovering the miRNA-mediated mechanism of fruit ripening and quality in this nutritional food.